Violetta - Biermann, Pieke 1950- (Mask noir ., 1996)
Bad enough to spend a summer holiday being ogled by overweight men well past their sell by date, even worse to come back to one's desk and find out that Berlin's serial killers have not been on vacation. There's the Stamper who tracks down foreign women, stranglers them and stamps T for Turk, C for Chilean, P for Pole on their forehead. Another murderer kills men, after sex, with a carate chop to the neck. And then there's the militant JoAnne Little Brigade, taking revenge on men for violence against women...